(untitled) (Annals of Bangladesh Agriculture, 2025)
The purpose of the study was to assess the perception of urban residents on rooftop gardening in Dhaka Metropolitan Area (DMA). The study was conducted by surveying 63 rooftop gardeners from Uttara and Mirpur of DMA. Primary data were collected using a pre-tested structured interview schedule. Findings revealed that most of the respondents of the study area were old-aged retired professionals having post-graduate education and moderate experience and knowledge on rooftop gardening. Friends, Facebook, and extension agents are top-ranked information sources. Majority of the respondents developed their gardens on the rooftop of their own houses, utilized 40-80% of their rooftop space for gardening, spent 2-3 hours daily in rooftop gardening, and planted a large number of vegetables (32), fruits (40), spices (11), flowers (48), and medicinal plants (12) in their rooftop gardens. Receiving safe and nutritional food for the family members, air quality development, and development of family mental health were the topmost perceived benefits of rooftop gardening by the respondents. Perception of the respondents on rooftop gardening was positively related to their experience in gardening, initial cost spent for garden development, contact with information sources, knowledge, and total species cultivated on rooftop gardening. Concerns about losing open spaces for kids to play due to rooftop gardening, difficulties in the collection of quality seeds and seedlings, lack of proper training and technical guidance on rooftop gardening were the major problems faced by the respondents. Developing guidelines on building code and structure to eliminate the misperception of damping and load-bearing capacity may enhance the further development of rooftop gardening in DMA. Ann. Bangladesh Agric. 28(2): 89-111